Exploring the Bacterial Impact on Cholesterol Cycle: A Numerical Study - Bourgin, Mélanie; Labarthe, Simon; Kriaa, Aicha; Lhomme, Marie; Gérard, Philippe; Lesnik, Philippe; Laroche, Béatrice; Maguin, Emmanuelle; Rhimi, Moez (Frontiers in Microbiology, 2020)
High blood cholesterol levels are often associated with cardiovascular diseases. Therapeutic strategies were developed to control cholesterolemia in human, targeting different functions involved in cholesterol transport or synthesis. However, the gut microbiota is also involved in cholesterol regulation by direct biotransformation of luminal cholesterol or conversion of bile salts, opening the way to the design of new strategies to manage cholesterol levels. In this report, we developed for the first time a whole-body human model of cholesterol metabolism including the gut microbiota in order to investigate the relative impact of host and microbial pathways. We first used an animal model to investigate the ingested cholesterol distribution in vivo. Then, using in vitro bacterial growth experiments and metabolite measurements, we modeled the population dynamics of bacterial strains in the presence of cholesterol or bile salts, together with their bioconversion function. Next, after correct rescaling to mimic the activity of a complex microbiota, we developed a whole body model of cholesterol metabolism integrating host and microbiota mechanisms. This global model was validated with the animal experiments. Finally, the model was numerically explored to give a further insight into the different flux involved in cholesterol turn-over. According to this model, bacterial pathways appear as an important driver of cholesterol regulation, reinforcing the need for development of novel ’bacteria-based’ strategies for cholesterol management.